Thymectomy for myasthenia and Thymoma: Peshawar Experience of 63 cases - Bilal, Amir; Saleem, Muhammad (Journal of Postgraduate Medical Institute, 2011)
To determine the safety and efficacy of thymectomy is thymomas and myasthenia gravis. A prospective observational study was carried out at Cardiothoracic Surgery unit LRH, Peshawar from march 1997 to April 2000. A total of 63 patients with a male and female ratio of 23:40 age range 15 - 50 years (Mean age 30.5 years) were entered into the study. Thirty nine presented with myasthenia while 24 presented with a mediastinal mass. They all underwent thymectomy via median sternotomy. Thymectomy in a thoracic surgical unit, with ventilatory backup, is a safe and effective treatment for both myesthenias and non myasthenics with thymomas, and stops the progress of an other wise crippling and fatal disease.